Strategy for Development of Ecological Citizens by Walhi Yogyakarta through Community-Based Education in Communities Gunung Sewu - Feri Taupik Ridwan; Dewi Gunawati; Rini Triastuti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The issue of environmental damage is one of the issues of global concern, occurring in almost all countries. Indonesia is one of the countries that have experienced environmental crises in a row every year. Burning forests, pollution and garbage are some things that until now have not found the right solution. This was compounded by the emergence of infrastructure development that escaped ecological awareness, both in the construction of roads, airports and expansion of urban areas. Environmental damage occurs almost everywhere, including the Gunung Sewu karst area which is threatened by mining and tourism. There are several factors causing environmental damage including the lack of ecological education programs carried out by the government to the community, the role of schooling that has not been optimal in environmental-based learning to the level of public awareness that is still low on sustainable development. Therefore it is important to form ecological citizenship that is responsible and able to be wise in protecting, managing and destroying the environment. From the point of view of Civic Education (Civics) the effort is an effort to develop civic virtue within the scope of Ecological citizenship. This study aims to determine the efforts made by the Yogyakarta walhi in conducting guidance to the Gunung Sewu community in the preservation of the Gunung Sewu karst area. The research method uses a qualitative approach. Research informants were members of the Yogyakarta walhi and Gunung Sewu Community. This research will show a variety of community development programs that include community development, providing information to the community and socialization of the preservation of the Gunung Sewu karst